2012
DOI: 10.15232/s1080-7446(15)30384-3
|View full text |Cite
|
Sign up to set email alerts
|

Smooth bromegrass pasture beef growing systems: Fertilization strategies and economic analysis

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 7 publications
0
40
1
Order By: Relevance
“…Watson et al (2012) found that cattle grazing unfertilized smooth bromegrass pastures had 25% less dietary CP (133 g CP kg −1 ) than cattle grazing N-fertilized smooth bromegrass pastures (179 g kg −1 ) at ENREC. Watson et al (2012) found that cattle grazing unfertilized smooth bromegrass pastures had 25% less dietary CP (133 g CP kg −1 ) than cattle grazing N-fertilized smooth bromegrass pastures (179 g kg −1 ) at ENREC.…”
Section: Dietary Nutritive Value and Dung Qualitymentioning
confidence: 96%
See 1 more Smart Citation
“…Watson et al (2012) found that cattle grazing unfertilized smooth bromegrass pastures had 25% less dietary CP (133 g CP kg −1 ) than cattle grazing N-fertilized smooth bromegrass pastures (179 g kg −1 ) at ENREC. Watson et al (2012) found that cattle grazing unfertilized smooth bromegrass pastures had 25% less dietary CP (133 g CP kg −1 ) than cattle grazing N-fertilized smooth bromegrass pastures (179 g kg −1 ) at ENREC.…”
Section: Dietary Nutritive Value and Dung Qualitymentioning
confidence: 96%
“…Cattle exhibit a partial preference for legumes relative to grasses (Boland et al, 2011;Villalba et al, 2015), and in mixed grass-legume swards, they select legumes at greater proportions than offered (Wen et al, 2004). These differences were expected to increase from June to August as dietary nutritive value (Watson et al, 2012) and dung quality (Lysyk et al, 1985) decrease in smooth bromegrass pastures and legume proportions increase. We hypothesized that cattle grazing legume-interseeded smooth bromegrass pastures would select diets with greater CP and in turn produce dung that has greater quality, decomposes faster, and increases nutrient movement into soil relative to diets and dung from N-fertilized and unfertilized smooth bromegrass monocultures.…”
mentioning
confidence: 99%
“…Research with smooth bromegrass has evaluated effects of fertilizer N inputs and application strategies on ANR and NUE, defined as forage DM production per unit of N fertilizer applied (Colville et al, 1963; George et al, 1973; Zemenchik and Albrecht, 2002). Recent research efforts have focused on increasing animal NUE through dietary supplementation strategies that increase body mass (protein) gains while reducing N fertilizer inputs to pastures (Greenquist et al, 2011; Watson et al, 2012). For pasture‐based systems, however, there is a knowledge gap on forage N responses to ruminant urine input and whether responses depend on N fertilizer rate.…”
Section: Useful Conversionsmentioning
confidence: 99%
“…Stocking rates in animal unit days (AUD) ha -1 were adjusted for herbage productivity and supplementation. Stocking rates after adjustments for put-and-take cattle averaged 256, 399, and 387 AUD ha -1 in CONT, SUPP, and FERT, respectively, during the first 5 yr of the experiment (Watson et al, 2012) and 222, 345, and 345 AUD ha -1 in CONT, SUPP, and FERT, respectively, in 2010 and 2011 . The initial stocking rate in SUPP was the same as in FERT because feeding DDGS reduced herbage dry matter (DM) intake in SUPP relative to FERT (i.e., 7.4 kg AUD -1 vs. 10.2 kg AUD -1 ) and compensated for the estimated 30% reduction in herbage productivity due to no fertilization.…”
Section: Litter Decomposition and Nutrient Disappearancementioning
confidence: 99%
“…With increasing costs of N fertilizer application and risks of N losses to the environment, however, efforts have been underway to increase N use efficiency in forage-based livestock production (Greenquist et al, 2011). Early research showed steers in SUPP had better body weight gains and used N more efficiently than steers in CONT and FERT (Greenquist et al, 2009;, and the SUPP management strategy produced greater economic returns because of reduced N fertilizer costs and improved animal performance (Watson et al, 2012). Early research showed steers in SUPP had better body weight gains and used N more efficiently than steers in CONT and FERT (Greenquist et al, 2009;, and the SUPP management strategy produced greater economic returns because of reduced N fertilizer costs and improved animal performance (Watson et al, 2012).…”
mentioning
confidence: 99%